[Petition for the LGBTQIA Faculty Staff Association to be recognized on campus] - Erin Echols::::::author::: (2011)
The letter is addressed to President Armstrong, asking him to formally recognize the Cal Poly LGBTQIA Faculty and Staff Association as a group on campus.